Perancangan Sistem Informasi Penggajian Karyawan Berbasis Web dengan Menggunakan PHP dan MySQL pada CV. Sukses Sejahtera - Sugiarti, Jeni; Sukarno, Hasbi Basith; Kusumadiarti, Rini Suwartika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The research aimed to know the system that is running, analyze design and build the accounting information system employee payroll at CV. Sukses Sejahtera. The research method used descriptive qualitative and data collection techniques used are observation, interviews, and literature reviews. System development method used is waterfall method. This accounting information system design used PHP and connect with MYSQL as database. The problem before making this system was data employee payroll still recorded manual in Microsoft Office Excel so this system not efficient, too much time to be wasted on recording or processing. The solution needed is to design a new payroll information system to make it easier to process data and generate reports quickly, precisely, and accurately.